Optimizing Geometric Alignment of High-Speed Railway in Hazard-Prone and Topographically Challenging Regions: A Case Study of the Bandung–Cirebon Corridor, Indonesia - Aghastya, Adya; Yudha, Aldi Wardana (Tecno Scientifica Publishing & Society of Tropical Science and Technology, 2025)
The development of high-speed rail (HSR) infrastructure in Indonesia, particularly along the Bandung–Cirebon corridor, required precise geometric planning to ensure operational efficiency, safety, and long-term performance. This study aimed to design an optimized alignment for the Phase III segment between Ligung and Tengahtani by integrating engineering criteria with spatial and environmental constraints. A descriptive-analytic method was employed, combining field surveys, Digital Elevation Model Nasional (DEMNAS) data, and spatial planning documents, which were processed using Global Mapper and AutoCAD Civil 3D to generate alignment models, earthwork calculations, and spatial risk assessments. The proposed design featured five main horizontal curves with radii ranging from 2,500 to 12,000 meters and fourteen vertical curves with a constant 25,000-meter radius, meeting technical standards for a maximum operational speed of 350 km/h. Earthwork estimation yielded approximately 4.82 million m³ of excavation and 47,208 m³ of fill, while land acquisition requirements totaled around 1.83 million m², primarily affecting agricultural and residential zones. Spatial analysis identified 1.64 million m² of the proposed corridor as being located in moderate- to high-seismic-hazard zones, emphasizing the need for structural mitigation strategies and geotechnical monitoring. The findings highlighted the critical importance of integrating geometric design with topographical and hazard data in planning resilient HSR infrastructure. This study provided a replicable framework for railway alignment in complex terrain and supported sustainable transportation development in Indonesia’s rapidly evolving intercity network.